Answer:
y = -8
Step-by-step explanation:
Y2 - Y1/ X2 - X1
-8 - (-8) / -1 - (-8)
0 / 7
m = 0
y = mx + b
-8 = 0(-8) + b
-8 = 0 + b
-8 = b
y = -8
y =2/x^(2) + 3
One possible answer is:
f(x) = (2/x) + 3 and g(x) = x².
Explanation:
We are to write this equation as y = f(g(x)). This means we want it to be a composite of functions; in f(x), we take the value of g(x) and use in place of x.
If we let g(x) = x², this means everywhere we see an x in f(x), we will replace it with x². To make our equation y = 2/x² + 3, working backward we would substitute x for x²; this would give us f(x) = 2/x + 3.
Answer:
sometimes
Step-by-step explanation: